Artificial rabbits optimization: A new bio-inspired meta-heuristic algorithm for solving engineering optimization problems - Wang, Liying; Cao, Qingjiao; Zhang, Zhenxing; Mirjalili, Seyedali; Zhao, Weiguo (Engineering applications of artificial intelligence, 2022)
In this paper, a new bio-inspired meta-heuristic algorithm, named artificial rabbits optimization (ARO), is proposed and tested comprehensively. The inspiration of the ARO algorithm is the survival strategies of rabbits in nature, including detour foraging and random hiding. The detour foraging strategy enforces a rabbit to eat the grass near other rabbits’ nests, which can prevent its nest from being discovered by predators. The random hiding strategy enables a rabbit to randomly choose one burrow from its own burrows for hiding, which can decrease the possibility of being captured by its enemies. Besides, the energy shrink of rabbits will result in the transition from the detour foraging strategy to the random hiding strategy. This study mathematically models such survival strategies to develop a new optimizer. The effectiveness of ARO is tested by comparison with other well-known optimizers by solving a suite of 31 benchmark functions and five engineering problems. The results show that ARO generally outperforms the tested competitors for solving the benchmark functions and engineering problems. ARO is applied to the fault diagnosis of a rolling bearing, in which the back-propagation (BP) network optimized by ARO is developed. The case study results demonstrate the practicability of the ARO optimizer in solving challenging real-world problems. The source code of ARO is publicly available at https://seyedalimirjalili.com/aro and https://ww2.mathworks.cn/matlabcentral/fileexchange/110250-artificial-rabbits-optimization-aro. •A new bio-inspired artificial rabbits optimization (ARO) algorithm is proposed.•ARO is inspired by the survival strategies of rabbits in nature.•The results on 31 well-known test functions show the efficiency of ARO.•ARO yields superior results over its competitors on 5 engineering problems.•ARO is successfully applied in fault diagnosis of rolling bearing.